Harvesting of residuary thermal energy from Mg modified BNT-BKT pyroelectric solid solution using Olsen cycle. (December 2022) - Kaur, Shubhpreet; Arora, Mehak; Kumar, Sunil; Malhi, Parambir Singh; Singh, Mandeep; Singh, Anupinder
Abstract: The incessant necessity of self-powered applications such as bio-medical devices, a wireless sensor etc has driven the request for high-production lead free pyroelectric materials towards energy harvesting. Herein, magnesium substituted bismuth sodium potassium titanate pyroelectric systems (Bi0.50 Na0.41 K0.09 )(Ti1- x Mgx )O3 where x = 0, 0.01 and 0.02 was synthesized. An indispensable role of magnesium on structural, microstructural and dielectric properties has been investigated. The co-existence of rhombohedral and tetragonal phase is confirmed by the X-ray diffraction pattern. The ferroelectric to relaxor/antiferro-electric phase transition was observed to be decrease from 150 °C to 76 °C with increase in doping from 0% to 2% respectively. Thereafter, the Olsen cycle was performed on the ferroelectric loops to demonstrate the energy harvesting properties of fabricated materials. The maximum of 475 mJ cm −1, 479 mJ cm −1 and 588 mJ cm −1 heat energy has been harvested from x = 0, 0.01 and 0.02 samples respectively. The Present work un-plug the various opportunities to develop high-performance pyroelectric energy harvester by utilizing lead free materials. Graphical Abstract: ga1